SCIENTOMETRIC STUDY ON THE PARASITOLOGY OF FRESHWATER FISH IN BRAZIL - Karling, Letícia Cucolo (2014)
This study presents the current state of research of freshwater fishes' parasites in Brazil, exploring the watersheds requiring further studies. The articles used were obtained through searching the databases ISI and SciELO, as well as direct search in the Curricula Vitae of researchers in this area. The survey was conducted during the month of March 2012 and 685 articles were obtained. The most studied group was Monogenea. Taxonomy was the most common studied subject. The most reported river basin is the Amazon region and the region of Parana. The largest concentration of periodic articles was Memorias do Instituto Oswaldo Cruz. Most articles were published in journals with Qualis B1 and B2 and without impact factor. More than half of the articles were found in the Curriculum of researchers. It is believed that this information will contribute to the knowledge of the available literature on this subject, offering subsidies to agencies that support research in the country and identifying geographical sampling gaps. Moreover, it allows the design of future biogeographic and ecological studies in order to assist in understanding the patterns of biological diversity of several groups of parasites in Brazil.